A CRITICAL REVIEW OF BLOOM’S TAXONOMY IN CONTEMPORARY EDUCATIONAL PRACTICES - Mykola Petrenko; Serhii Melnyk; Iryna Kovalenko; István Kovács; Anikó Tóth; Miklós Horváth; Judit Szabó (International Journal of Education and Social Science Studies, 2026)
Bloom’s Taxonomy has been a cornerstone of educational theory, providing a structured framework for defining learning objectives, designing curricula, and aligning assessments. This study offers a novel critical perspective by integrating contemporary pedagogical frameworks into the evaluation of Bloom’s Taxonomy and applicability in contemporary educational practices. This study employs a critical literature review method to examine, including technology-enhanced, collaborative, and project-based learning environments. The analysis, based on thematic synthesis, identifies key strengths, such as clarity, systematic organization of cognitive skills, and adaptability for instructional design, alongside significant limitations, including insufficient attention to affective and socio-emotional domains and emerging 21st-century competencies like digital literacy, creativity, and collaborative problem-solving. Furthermore, gaps between theoretical revisions and practical classroom implementation are highlighted, particularly regarding empirical evidence of effectiveness in modern learning contexts. The study concludes that while Bloom’s Taxonomy remains a foundational tool, its continued relevance depends on adaptive, flexible, and context-sensitive applications that integrate cognitive, affective, and psychomotor domains while addressing contemporary educational needs. The study recommends integrating digital literacy, collaborative learning strategies, and affective assessment into taxonomy-based instructional design, fostering holistic student development, critical thinking, creativity, and digital competence. The findings underscore the necessity of bridging theory and practice to ensure the taxonomy’s effectiveness in supporting 21st-century learning outcomes.